Factors Affecting Outcome of Information Technology (IT) Solution Deployment Projects - Perera, Mr. Manjula (My University, 2011)
The extent of the successfulness of an organization's information systems (IS) starts at the very beginning, even before it is implemented. In other words the success of a system would be determined at the starting point of its implementation; from identification of requirements to the final implementation and go live phase. Hence the sequence of activities occurring according to a pre-plannedschedule is of utmost importance. The related literature shows that there is a very big potential in InformationTechnology (IT) growth in Sri Lanka, hence making it even more importantto complete IT systems projects successfully, for the betterment of the country as a whole.Past recordsshows that there is high tendency of IT project failure in many areas around the world, making it important to identify the main factors which affects IT project outcomes; especially in terms of its success, and concentrate on these with the vision of completing the project in a timely, cost effective manner which ensures stakeholder expectations. The main objective of this research is to identify and rate the main project success, challenged and impaired factors according to their importance, which in turn would provide a check list for project managers to practice in future IT related projects, in. Sri Lanka. A structured questionnaire was used to collect data from participants of selected IT related solution providers in Sri Lanka. Answers received from 497 respondents were analyzed. The overall response rate was 66 percent. The deductive mode of reasoning, cross-sectional study and quantitative techniques were selected as main research methods. The results of the survey showed the identified factors according to their importance in each separate area, which formed the final check list of factors. By giving proper attention to all these factors according to their importance, the management of an organization will be able to have some space to think and plan out their IT related project activities which in turn would lead to a successful project closure.